KEDUDUKAN HUKUM ADAT SEBAGAI ATURAN HUKUM NASIONAL DALAM SISTEM HUKUM INDONESIA - Patricia, Tiara; Gunawan, Chyntia; Selly, Jeane N. (Lex Librum : Jurnal Ilmu Hukum, 2025)
The position of customary law within Indonesia’s legal system remains significant, and various domains of adat law continue to play an essential role in addressing contemporary issues and conflicts in the era of globalization. This article relies primarily on secondary data, gathered through literature review, examination of relevant legal sources, and online research pertaining to the subject matter. The data obtained are qualitative in nature. In terms of its standing, customary law holds an equal place to other legal norms within Indonesia’s legal framework, although its application is limited to Indonesian citizens and it remains unwritten. The 1945 Constitution acknowledges the existence of adat law as an unwritten legal system, yet the state prioritizes statutory written law such as legislation to maintain public order and legal certainty. Certain areas of adat law, such as customary inheritance and land law, remain particularly relevant today. Adat law embodies behavioral norms governing Indigenous Indonesians, is not codified into formal statutes, and carries binding force. In the formation of laws or qanuns in Aceh, legislative bodies are required to consider customary law as it represents the living legal consciousness of the community.